A Rare Case of Fibrous Hamartoma of Infancy: A Clinicopathological Diagnosis at a Tertiary Hospital, Eastern Nepal - G. Lama; P. Upadhyaya; B. Adhikari; M. Adhikari; S. Dhakal (Hindawi Limited, 2019)
Background. Fibrous hamartoma of infancy is a rare soft tissue lesion of infants and young children with characteristic triphasic morphology. Case Description. An 18-month-old female child was presented with complaints of swelling over right leg shin since birth. On examination, a lump of size 7x3 cm was identified which was mobile and nontender. Local excision was performed and tissue sent for histopathological examination. On gross examination, a globular, capsulated, firm to hard tissue had cut section revealing solid grey-white to grey-brown lesion with myxoid areas identified. Microscopic examination revealed a poorly circumscribed lesion comprising intersecting trabeculae of fibrous tissue, areas of immature oval and stellate cell within myxoid matrix, and varying amounts of interspersed mature fat cells. Conclusion. Even though fibrous hamartoma of infancy is a rare benign entity with limited clinical knowledge, proper diagnosis is mandatory as its prognosis is excellent.